Relationship between salivary IgA secretion and upper respiratory tract infection following a 160-km race - Nieman, D. C.; Henson, D. A.; Dumke, C. I.; Lind, R. H.; Shooter, L. R.; Gross, S. J. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The relationship between salivary IgA secretion rate and upper respiratory tract infection (URTI) was studied in 155 ultramarathoners (126 males, 29 females, mean age 46.5±0.7 y) who had qualified to run the 160-km 2003 Western States Endurance Run. Methods: Subjects provided saliva samples during registration, held the morning before the race, and within 5-10 minutes postrace (mean race time, 26.2±0.3 h). Unstimulated saliva was collected by expectoration for 4 minutes into 15-mL plastic, sterilized vials. Runners finishing the race and providing pre- and postrace saliva samples (n=106) turned in a health log specifying URTI episodes and severity of symptoms for the 2-week period following the race. Results: The total volume of saliva that the runners was able to expectorate during sample collection decreased 51% postrace compared to prerace values (P<0.001). Saliva protein concentration increased 20% (P<0.001) while the saliva protein IgA concentration decreased 10% (P<0.05). Salivary IgA secretion rate decreased 46% when comparing pre- to postrace values (P<0.001). Twenty-four percent of the runners finishing the race and providing salivary samples reported an URTI episode lasting 2 days or longer during the 2-week period following the race (mean number of days with symptoms was 5.4±0.6 days). The decrease in salivary IgA secretion rate (pre- to postrace) was 53% greater in the 25 runners reporting URTI (-355±45 µg/min) compared to the 81 runners not reporting URTI (-232±37 µg/min), (P=0.04). Conclusion: In summary, nearly 1 in 4 runners reported an URTI episode during the 2-week period following a 160-km race, and the decrease in salivary IgA secretion rate was significantly greater in these runners compared to those not reporting URTI.